Optimizing Pricing Strategies for Propane Market : An empirical field-experiment study on price elasticity and consumer behaviour in Finland - Säkkinen, Joonas (My University, 2026)
Pricing decisions are central to profitability in consumer energy markets, yet empirical evidence from automated retail channels remains scarce. This thesis examines how alternative pricing strategies affect demand and revenue for liquefied propane gas (LPG) cylinders sold through self-service vending machines in Finland. A four-month field experiment across 41 machines imple-mented three treatments—price increase (+10%), price decrease (−10%), and dynamic pricing—alongside a control group. The primary analysis focuses on experimental treatment comparisons versus the control group using year-over-year (YoY) price/volume analysis, while weekly panel regression is used as a secondary analysis to summarize price–quantity co-movement and ex-plore demographic interactions. In the experimental comparisons, realized average prices (revenue/quantity) confirm that the treatments were implemented as intended relative to the control group. The control group expe-rienced only small, realized price changes (5kg +2.4%; 10kg +1.4%), whereas the +10% treatment achieved the largest uplift (5kg €19.19 → €21.37, +11.4%; 10kg €27.31 → €30.09, +10.2%). Rela-tive to the control group’s YoY revenue change (−26.1%), the +10% treatment showed a smaller decline (−20.5%), while dynamic pricing performed worse (−32.9%) despite its realized price in-creases (5kg +8.3%; 10kg +9.3%). The −10% group is reported, but interpretation is cautious be-cause some machines were reassigned during the trial period, reducing identification strength for that trial group. Overall, the experimental evidence indicates that stable price uplift can improve outcomes relative to the control group, whereas frequent price changes under dynamic pricing coincide with weaker performance in this self-service channel. Weekly log–log OLS regression is presented as a secondary analysis. The models have moderate fit (R² ≈ 0.222 for 5kg and 0.219 for 10kg; n = 678 observations per product), but the baseline price coefficient in the control group is positive and statistically significant (β₁ ≈ 2.304 for 5kg; β₁ ≈ 2.404 for 10kg). This unexpected sign is interpreted as likely reflecting peak-season co-movement and omitted time-varying factors (e.g. weather) affecting both realized prices and quantities, rather than a structural demand response or true upward-sloping demand. Demo-graphic interaction terms (income and population) are generally weak. Managerially, the results support transparent and stable pricing as the default approach in propane vending, recommend caution in implementing dynamic pricing without robust and clearly defined rule-sets, and sug-gest reserving discounts for targeted and strategically justified use.

Hinnoittelupäätökset ovat keskeisiä kuluttajamyynnin kannattavuudelle energiasektorilla. Silti empiiristä näyttöä automatisoiduista vähittäismyyntikanavista on niukasti. Tässä tutkielmassa tarkastellaan vaihtoehtoisten hinnoittelustrategioiden vaikutusta itsepalveluautomaattien kautta myytävän nestekaasun kysyntään ja myyntiin Suomessa. Nelikuisessa kenttäkokeessa 41 automaatilla testattiin kolmea strategiaa: hinnankorotusta (+10%), hinnanalennusta (−10%) ja dynaamista hinnoittelua. Ensisijaisesti analysoidaan testiryhmiä suhteessa kontrolliryhmään hyödyntäen vuoden takaiseen vertailuun perustuvaa hinta-/volyymianalyysiä. Toissijaisena metodina käytetään viikoittaista paneeliregressiota, jossa tarkastellaan hinnan ja volyymin yhteisvaihtelua sekä tarkastellaan demografisten tekijöiden vaikutuksia. Vertailuissa toteutuneet keskihinnat (liikevaihto/volyymi) vahvistavat, että hinnanmuutokset toteutettiin suunnitellusti suhteessa kontrolliryhmään. Kontrolliryhmässä toteutuneet hinnanmuutokset olivat pieniä (5kg +2.4%; 10kg +1.4%), kun taas +10%-ryhmä tuotti suurimman nousun (5kg €19.19 → €21.37, +11.4 %; 10kg €27.31 → €30.09, +10.2%). Kontrolliryhmän YoY-liikevaihdon muutokseen (−26.1%) nähden +10%-ryhmän lasku oli pienempi (−20.5%), kun taas dynaaminen hinnoittelu suoriutui heikoiten (−32.9%) toteutuneista hinnoista huolimatta (5kg +8.3 %; 10kg +9.3 %). −10%-ryhmän tuloksia tulkitaan harkiten, sillä automaattien siirto toisiin ryhmiin kesken kokeen on saattanut heikentää tulosten luotettavuutta. Kaikkiaan kokeellinen näyttö viittaa siihen, että vakaa hinnankorotus voi parantaa tuloksia suhteessa kontrolliryhmään, kun taas dynaamisen hinnoittelun toistuvat hinnanmuutokset voidaan yhdistää heikompaan suoriutumiseen kyseisessä myyntikanavassa. Viikoittaisten log–log OLS -regressiomallien selitysaste on kohtalainen (R²≈0.222 5kg:lle ja 0.219 10kg:lle; n=678 havaintoa per tuote), mutta vertailuryhmän hintakerroin on positiivinen ja tilastollisesti merkitsevä (β₁≈2.304 5kg:lle; β₁≈2.404 10 kg:lle). Odottamaton tulos voitaneen tulkita huippusesongin aikaiseksi yhteisvaihteluksi sekä puuttuvien tekijöiden (esim. sää) vaikutukseksi ennemmin kuin rakenteelliseksi kysynnänmuutokseksi tai todelliseksi nousevaksi kysyntäkäyräksi. Demografisten tekijöiden (tulot ja väestö) vaikutukset ovat pääasiassa heikkoja. Päätöksenteon tueksi tulokset suosittelevat läpinäkyvää ja vakaata hinnoittelua, varovaisuutta dynaamisen hinnoittelun käyttöönotossa ilman ennalta määriteltyjä ehtoja sekä kohdentamaan alennukset tarkasti ja strategisesti perustellusti.
Keywords: pricing; consumer behaviour; price elasticity; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management